Possible Tracheal Relaxant and Antimicrobial Effects of the Essential Oil of Ethiopian Thyme Species (Thymus serrulatus Hochst. ex Benth.): A Multiple Mechanistic Approach - Rehman, Najeeb Ur; Ansari, Mohd Nazam; Haile, Tesfay; Karim, Aman; Abujheisha, Khalil Y; Ahamad, Syed Rizwan; Imam, Faisal (Frontiers in Pharmacology, 2021)
The genus Thymus is traditionally used for the treatment of hyperactive airways complaints. The purpose of the current study is to investigate the potential tracheal relaxant effect and possible mechanism(s) of the essential oil of Thymus serrulatus (TS Oil) in isolated guinea pig tracheal tissues. The essential oil was obtained from the fresh erial parts of Thymus serrulatus, and its phyto-components were identified by GC-MS analysis. Guinea pig tracheal preparations were used for testing the tracheal relaxant effect of TS Oil with the determination of the mechanism(s) involved in this relaxation. GC-MS findings reveal that terpenes, fragrance constituents, saponins, and higher fatty acids are present in TS Oil. In isolated guinea pig trachea, TS Oil inhibited carbachol (CCh, 1 µM) and K+ (80 mM)-induced contractions in a pattern similar to that of dicyclomine. TS Oil, at 0.3 mg/ml, shifted parallel CCh-curves towards the right, followed by a non-parallel shift at higher concentration (1 mg/ml), thus suppressing maximum response in the same manner as produced by dicyclomine. Pretreatment of tissues with TS Oil (1 and 3 mg/ml) also produced a rightward shift of Ca++ concentration-response curves (CRCs) in the same manner as caused by verapamil. Further, TS Oil at low concentrations (0.3 and 1 mg/ml) shifted isoprenaline-induced inhibitory CRCs towards the left and increased cAMP levels in isolated tracheal homogenates similar to papaverine, a phosphodiesterase (PDE) inhibitor. In the antimicrobial assay performed by the agar well diffusion method, TS Oil was found most active against Candida albicans and Staphylococcus aureus where the zone of inhibition measured was 28 mm. Additionally, there was little difference between standard strains of gram-positive and gram-negative bacteria. However, methicillin-resistant S. aureus (MRSA) showed a small zone of inhibition as compared to standard strains (22 mm). From these results, it can be concluded that the essential oil of T. serrulatus has the potential to produce antimicrobial effects while causing tracheal relaxation mediated possibly by anticholinergic effects, Ca++ channel blockade, and PDE inhibition whereas additional mechanism(s) cannot be ruled out.